Feasibility analysis of GRIDSOL technology in Fuerteventura: A case study. Issue 18 (1st July 2019) - Fedato, E.; Baldini, M.; Dalla Riva, A.; Mora Alvarez, D. F.; Wiuff, A.K.; Hethey, J.; Cerrajero, E.; Estebaranz, J.M.
Abstract : The power sector is experiencing a considerable transformation, shifting primary sources of energy production towards more sustainable alternatives. Despite the benefits, the increasing penetration of renewable raised concerns in terms of intermittency and unpredictability of electricity production, challenging the balance between demand and supply. To this end, the GRIDSOL project proposes Smart Renewable Hubs designed to provide a single and steady output of electricity combining different renewable and storage technologies such as concentrated solar power, photovoltaic, electrical and thermal batteries. This study investigates the technical application and economic feasibility of GRIDSOL for the case of Fuerteventura. Based on different technology configurations, the outcomes show a relevant role of the concentrated solar power plant, replacing diesel plants for electricity generation. In one configuration, GRIDSOL can provide up to 68% of the energy consumption, with a capacity factor of 67% for the concentrated solar power plant and a 24% CO2 emission reduction compared to 2016 levels. The economic assessment, performed over different scenarios, shows that the applicability of GRIDSOL in the Canary system requires support in terms of investments grants on the capital expenditure (58% of the costs) or as feed‐in premiums on energy production (54–67 €/MWh) to break‐even.